KEEFEKTIFAN TEKNIK MODELING DALAM BIMBINGAN KELOMPOK UNTUK MENINGKATKAN DISIPLIN BELAJAR SISWA DI MA SA DARUL ISTIQOMAH - Ali Ahsanul Kholiqin; Zeti Novitasari; Wahyu Setia Kuscahyaning Putri (Jurnal Ilmiah Hospitality, 2020)
Education is something that can not be separated from human life. Problems in applying the discipline of learning are often experienced by students. Student learning discipline is a key that can create a conducive and optimal learning atmosphere. Based on preliminary observations at MA SA Darul Istiqomah shows that there are students who commit violations of school rules. As for the violations that are often done by students such as being late for school, not wearing neat uniforms, disposing of trash improperly. Learning discipline is a form of obedience to the rules, both written and unwritten that have been set. Modeling is learning through observation by adding or reducing the observed behavior, generalizing various observations at once, involving cognitive processes. This research uses a quantitative approach with a pre-experimental design. The research design used was one group pretest postest design. The average percentage of the six students before being treated was 52.15% and in the low category. The average percentage of the five students after being given treatment is 71.77% and is in the medium category. H0 is rejected and H1 is accepted which means there is an average difference between the students' pretest and posttest scores. Then the research can be concluded by applying group guidance services with effective modeling techniques to help improve the discipline of student learning in class XI MA MA SA Darul Istiqomah